(untitled) (Interfaces: A Journal of Medieval European Literatures, 2024)
The article examines the patronage of two neo-Latin poets from the early seventeenth century: the Bohemian humanist Venceslaus Clemens (1589–1637) and the Dutch writer and physician Johannes Narssius (1580–1637), both of whom produced long epics to celebrate the intervention of the Swedish king Gustavus II Adolphus in the Thirty Years’ War (1618–48). These two authors are suitable for a comparative analysis, because they both acted as favour seekers in a foreign country and they approached the same dedicatees. Although both writers were skilful epicists and their networks overlapped, Clemens was unsuccessful in securing funding from his honorandi, while Narssius received both remuneration and a career. By uncovering the two poets’ ultimate goals and their strategies to seek favour, I will argue that the system of patronage in which they operated was more complex than an unexperienced writer might have expected and that one of the poets featured here was not fast enough to grasp this system’s intricate mechanisms.